The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Encyclopedia of Inorganic and Bioinorganic Chemistry 2004
DOI: 10.1002/9781119951438.eibc0576
|View full text |Cite
|
Sign up to set email alerts
|

FeSuperoxide Dismutase

Abstract: Iron‐containing superoxide dismutases (FeSOD) are generally dimers of identical 21‐kDa monomers, each of which contains a single active site. Each active site binds one Fe ion with roughly trigonal bipyramidal geometry, employing two His and an Asp − residue as equatorial ligands, and one more His and a coordinated solvent as axial ligands. In the course of the catalytic cycle, the Fe alternates between the +3 and +2 states, and the coordinated solvent is believed to alternate between O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Furthemore, there are no significant differences between the three structures reported here. All present the five ligands (His28, His76, His165, Asp161 and a water molecule) spatially arranged in a trigonal bipyramid around the iron atom 26. Beyond the ligands themselves, the active site neighbourhood also shows the well‐conserved hydrogen bonding network involving Trp125, Gln72, Tyr36, His32, and Tyr168 from the vicinal subunit 59.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthemore, there are no significant differences between the three structures reported here. All present the five ligands (His28, His76, His165, Asp161 and a water molecule) spatially arranged in a trigonal bipyramid around the iron atom 26. Beyond the ligands themselves, the active site neighbourhood also shows the well‐conserved hydrogen bonding network involving Trp125, Gln72, Tyr36, His32, and Tyr168 from the vicinal subunit 59.…”
Section: Resultsmentioning
confidence: 99%
“…and in several bacterial genomes,19, 20 and present a distinct four‐helix antiparallel bundle topology 21, 22. The different SOD types posses a widespread distribution in both eukaryotic and prokaryotic cells, appearing either in the cytosol, periplasm or compartmentalized in organelles such as mitochondria and chloroplasts 15, 23–27. For instance, while the protozoan parasites P. falciparum , T. cruzi , and T. brucei present only different isoforms of the iron‐containing SOD, distributed in the cytosol, glycosomes, and mitochondria,11, 28–32 their host human cells possess a mitochondrial MnSOD33 and a cytosolic Cu‐ZnSOD.…”
Section: Introductionmentioning
confidence: 99%
“…ROS accumulation plays an important role in photoaging where antioxidant enzyme significantly declines on the corneum layer and increase the concentration of protein oxidation in the upper dermis (Miller, 2011). Our study showed SOD increased TAS value and sebum concentration while decreasing in TEWL.…”
Section: Discussionmentioning
confidence: 47%
“…Each subunit is composed of two domains: an α-helical N-terminal domain and a mixed α/β C-terminal domain. [43][44][45][46] The subunits have a single metal ion in the active site. The metal center is bound by equivalent residues, coordinated in trigonal bipiramidal geometry; two histidines and an aspartate residue occupy the equatorial plane with a histidine residue and a solvent molecule (water or hydroxide) occupying the axial positions.…”
Section: Fe and Mn Superoxide Dismutasesmentioning
confidence: 99%
“…Group 2; SODs that have an intervening fragment containing a short helix H2 between the two helices H1 and H3. (e.g., Fe-SODs from Escherichia coli 44 , cambialistic SOD from Porphyromonas gingivalis 39 ). Group 3; SODs with longer loop between H1 and H2 (e.g., Fe-SOD from Aquifex pyrophilus 134 ).…”
Section: Subunit Foldmentioning
confidence: 99%